Peran Guru dalam Memberikan Motivasi Belajar Siswa MIN 1 Pali - Asmuni; Afgani, Win; Afriantoni (Program Studi Magister Pendidikan Agama Islam, 2024)
This research aims to analyze the role of teachers in providing student learning motivation at MIN 1 Pali. Strengthening and instilling motivation to learn is in the hands of the teachers. Because apart from students, the most important element in learning activities is the teacher. Teachers are educators who play a role in pedagogical engineering. Who prepares learning designs and implements them in the teaching and learning proccess. Teachers are the core key in the learning process, both in improving the quality of education and in providing learning motivation to students. There are many factors why students are less motivated to learn, both external factors and factors within the students themselves. The type of research used is a qualitative descriptive method. This research was carried out in class 4 MIN 1 Pali, taking teachers and students as subjects. Data was obtained through observation, interviews, documentation and recording. The research results show that the teacher's role in providing learning motivation to students has been carried out optimally. The role of the teacher includes as a learning manager, the teacher is able to adjust to student conditions, the teacher as a guide, as a facilitator, as a mediator, as a motivator and as an evaluator. Abstrak Penelitian ini bertujuan untuk menganalisis peran guru dalam memberikan motivasi belajar siswa di MIN 1 Pali. Penguatan dan penanaman motivasi belajar berada di tangan para guru. Karena selain siswa, unsur terpenting yang ada dalam kegiatan pembelajaran adalah guru. Guru adalah pendidik yang berperan dalam rekayasa pedagogik. Yang menyusun desain pembelajaran dan dilaksanakan dalam proses belajar mengajar. Guru merupakan kunci inti dalam proses pembelajaran, baik dalam meningkatkan kualitas pendidikan maupun dalam memberikan motivasi belajar kepada siswa. Banyak sekali faktor siswa kurang termotivasi untuk belajar, baik faktor dari luar maupun faktor dari dalam diri siswa itu sendiri. Jenis penelitian yang digunakan yaitu metode deskriptif kualitatif. Penelitian ini dilaksanakan di kelas 4 MIN 1 Pali dengan mengambil subjek guru dan siswa. Data didapatkan melalui observasi, wawancara, dokumentasi, dan pencatatan. Hasil penelitian menunjukkan bahwa peran guru dalam memberikan motivasi belajar kepada siswa sudah dilakukan secara maksimal. Peran guru meliputi sebagai pengelola pembelajaran, guru mampu menyesuaikan kondisi siswa, guru sebagai pembimbing, sebagai fasilitator, sebagai mediator, sebagai motivator dan sebagai evaluator.